Analisis Semiotika Roland Barthes terhadap Representasi Disabilitas dan Ketangguhan dalam Konten Gritte Buka Praktek bersama Maureen - Ahyar Reza Supena (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines how the YouTube video "Gritte Buka Praktek" constructs meaning around disability through the story of Maureen, a woman living with severe scoliosis and a tracheostomy, using Roland Barthes's semiotic framework combined with a qualitative framing approach. At the denotative level, the video records an intimate dialogue between host Gritte Agatha and Maureen, marked by warm lighting, close-up shots, and a calm conversational rhythm. At the connotative level, the analysis identifies three dimensions shaping a transformative narrative: psychological resilience expressed through Maureen's body language and vocal tone; empathetic, non-paternalistic relationality between host and guest that positions Maureen as an autonomous subject rather than an object of pity; and cultural counter-discourse that dismantles the "perfect versus imperfect body" dichotomy. At the mythic level, the video naturalizes three ideological mythsunbreakable courage, happiness beyond physical limitation, and self-acceptance as emotional strengthwhich frame disability as a source of humanistic meaning. The findings show that the video shifts disability representation from a medical-individual model, centered on limitation and suffering, toward a socio-affirmative model that emphasizes agency and dignity, thereby contributing to a broader discourse of inclusivity in Indonesia's digital public sphere.